Distance learning and higher education in west francophone Africa: an university shaped from outside or renewed from inside ? - (:unkn) unknown (My University, 2007)
In most papers on education in Africa, distance learning is adorned with all the virtues and then, would be able to modernize the educational systems, to open university to new public, to reduce the costs of education, to bring up to standard the teachers, to increase the access to higher education. Projects with continental vocation, as African virtual university of the World Bank, are next to more geographically and culturally targeted devices, as french-speaking digital campuses and more modest initiatives, locally supported by individuals more than by institutions. Our opening coarse interrogation is doubtless “ what is the use of distance learning in Africa ?”. And then reveals another one, more delicate : “ which ambitions does distance learning serve ?”. Our main research hypothesis is that distance teaching can serve both to shape the university from outside that to renew it from inside.
Keywords: African Research